Britain's Health Services (London : Communist Party of Great Britain)
1942-10 1942 1940s 40 pages employed in hospitals, public services and in general practice, and a Committee on the lines suggested could heighten efficiency in all these services. (c) Other Services The previous examples of health work have been given particular attention because the measures proposed are realisable by the activities of workers themselves more easily, perhaps, than by the making of demands upon the Government or Local Authorities. The Communist Party is, however, well aware that a number of public health questions are not at present capable of solution in that manner. Health workers interested in the outstanding problems outlined in the following five paragraphs can assist in their solution by putting forward proposals, through Trade Union Branches and local organisations of the Labour and Co-operative movement, to their National Executives and so to Parliament, and in this way press for essential reforms. Tuberculosis The rapid increase of tuberculosis, particularly amongst young women, causes great anxiety. A committee of the Medical Research Council is investigating the matter, but has not yet issued a report. Workers affected by this disease will often not report sick till too late because of their fear of losing their job and (though sanatorium treatment is free) of having to exist during a long convalescence period on the inadequate National Health Insurance allowance plus what they can get if they apply for it through the Public Assistance Board. The untreated infected workers are a continuous danger to those in contact with them in the factories and at home. It is well recognised that the following measures are necessary:— The maintenance of a high level of nutrition amongst the more susceptible group — girls and young women — and control over their hours and conditions of work in the factories. Routine examination of the workers by mass radiography and the early hospitalisation of infected workers. Full pay for tuberculous cases during the period in which they are rehabilitated for duty. The Ministry of Labour scheme, which only pays workers during rehabilitation according to the amount of work they do, is if anything more unsatisfactory for tuberculous than for other workers. An assurance to patients that when they recover they will be restored to their jobs. 16 15X/2/103/252